Shear-Wave Elastographic Evaluation of Splenic Stiffness in Patients with Chronic Liver Diseases as A Predictor of the Oesophageal Varices Grade - Ahmed Faaz Nasser; Haider Najim Al-Tameemi (مجلة الكوفة الطبية)
Background: Chronic Liver disease (CLD) is a global public health problem and one of the leading causes of mortality worldwide with many complications like portal hypertension (PH) and esophageal varices (EV). Researchers have investigated the role of shear-wave elastography (SWE) as a non-invasive method to assess patients with cirrhosis and PH. However, studies evaluating the role of splenic stiffness (SS) have shown variable results. Aim of the study:  This study aims to assess the SS in a patient with CLD compared to controlled cases and to evaluate its role in the prediction of EV grade. Material and Methods. The study included 60 participants; 30 patients diagnosed with CLD by the clinical, laboratory, and radiological investigation, who underwent upper gastrointestinal endoscopy; and 30 control health individuals. The mean splenic size, SS, and platelet counts were measured for all participants. Mean SS was compared between two groups, and then its validity in differentiated between low and high-risk groups of EV was assessed. Results. Patients with CLD and controls were significantly different in SS values with cut-off value of 12.49 Kpa. Among CLD patients, the low and high-risk EV subgroups were significant different in SS values with cut-off value of 15.125 KPa. Compared with splenic size and platelet count, SS had the highest accuracy (93.3%) in predicting high-grade EV. Conclusion. Patients with CLD showed higher SS values than control with stepwise increase in SS with increasing grade of EV.  SS can accurately predict high-risk groups of EV hence may help decrease patients' burden by avoiding unnecessary endoscopy.